Carbohydrate utilization by herbivorous and omnivorous freshwater fish species: a comparative study on gibel carp (Carassius auratus gibelio. var CAS III) and grass carp (Ctenopharyngodon idellus). (14th May 2014) - Li, Xiangsong; Zhu, Xiaoming; Han, Dong; Yang, Yunxia; Jin, Junyan; Xie, Shouqi
Abstract: Two 8‐week feeding trials were conducted to evaluate dietary carbohydrate utilization by omnivorous gibel carp ( Carassius auratus gibelio ) (2.4 ± 0.1 g) and herbivorous grass carp ( Ctenopharyngodon idellus ) (6.5 ± 0.1 g). Five isonitrogenous (370 g kg −1 ) and isolipid (70 g kg −1 ) diets were formulated with increasing corn starch levels (60, 140, 220, 300 and 380 g kg −1 ). Results showed that specific growth rate (SGR), feed efficiency (FE) and protein retention efficiency (PRE) of gibel carp significantly increased from dietary starch of 60 to 300 g kg −1 and then decreased from 300 to 380 g kg −1, but those of grass carp showed no significant differences between treatments. Independent of dietary starch levels, grass carp gained significantly higher FE and PRE than gibel carp. Feeding rate (FR) of gibel carp was significantly higher than that of grass carp. In two fish species, high dietary starch (300 and 380 g kg −1 ) tended to obtain higher hepatosomatic index (HSI), serum triglyceride, hepatic lipid and body lipid contents. Serum glucose concentration of grass carp was not affected, while that of gibel carp fed the starch of 300 g kg −1 diet was significantly lower than those of the fish fed other four diets (60, 140, 220 and 380 g kg −1 ). Grass carp showed high tolerance to dietary starch while dietary corn starch should be no more than 300 g kg −1 for gibel carp. High starch contents may cause lipid accumulation in the liver and body.